Hydroclimatic and cultural instability in northeastern North America during the last millennium - Stager, J. Curt (PLoS One, 2021)
Long-term, large-scale perspectives are necessary for understanding climate variability and its effects on ecosystems and cultures. Tree ring records of the Medieval Climate Anomaly (MCA) and Little Ice Age (LIA) have documented major hydroclimatic variability during the last millennium in the American West, but fewer continuous, high-resolution hydroclimate records of the MCA-LIA period are available for eastern North America, particularly during the transition from the MCA to the LIA (ca. A.D. 1250–1400). Diatoms (micro-algae with silica cell walls) in sediment cores from three Adirondack (NY, USA) lakes and a hiatus in a wetland peat deposit in the Adirondack uplands provide novel insights into the late Holocene hydroclimate history of the Northeast. These records demonstrate that two of the region’s most extreme decadal-scale droughts of the last millennium occurred ca. A.D. 1260–1330 and ca. A.D. 1360–1390 during a dry-wet-dry (DWD) oscillation in the Adirondacks that contributed to forest fires and desiccation of wetlands in New York and Maine. The bimodal drying was probably related to more extreme droughts farther west and coincided with major events in Iroquoian and Abenaki cultural history. Although the causes of the DWD oscillation in the Adirondacks remain uncertain, changing sea-surface temperatures and solar variability are likely to have played a role.